On the Use of Model Order Reduction Techniques for the Elastohydrodynamic Contact Problem - Maier, Daniel (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2015)
The objective of this work is to develop a method which solves the nonlinear elastohydrodynamic contact problem in a fast and precise way using model order reduction techniques. The reduction procedure is based on a projection onto a low-dimensional subspace using different hyper-reduction procedures. The method provides fast and highly accurate reduced order models for stationary and transient, Newtonian and Non-Newtonian EHD line and point contact problems.